Analisis Kandungan Vitamin C dan Kadar Antioksidan Teh Kombucha Daun Pandan Wangi (Pandanus amaryllifolius) dengan Pemanis Stevia Berdasarkan Lama Fermentasi - Putri Meirani; Ambarwati Ambarwati; Dea Anisa Putri (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to analyze the vitamin C content and antioxidant levels of fragrant pandan leaves with stevia sweetener based on fermentation time, so as to obtain the most optimum vitamin C content and antioxidant levels in kombucha tea. The research method is experimental research, namely by varying the fermentation time in making kombucha tea. The results of the research show that the longer the fermentation process takes to raise the pH of kombucha tea, the clearer the color of the kombucha tea is, the longer the fermentation process takes. The optimum vitamin C content was obtained on the 13th day of fermentation at 14.67 mg/100 g, and the optimum antioxidant content was also obtained on the 13th day of fermentation at 77.94%. The results obtained from physical observations include color, taste, and aroma. Keywords: Antioxidants, Fermentation Time, Kombucha Tea, Vitamin C